Causal Cognition, Force Dynamics and Early Hunting Technologies - Gärdenfors, Peter; Lombard, Marlize (Frontiers in Psychology, 2018)
With this contribution we analyse ancient hunting technologies as one way to explore the development of causal cognition in the hominin lineage. Building on earlier work, we separate seven grades of causal thinking. By looking at variations in force dynamics as a central element in causal cognition, we analyse the thinking required for different hunting technologies such as stabbing spears, throwing spears, launching atlatl darts, shooting arrows with a bow, and the use of poisoned arrows. Our interpretation demonstrates that there is an interplay between the extension of human body through technology and expanding our cognitive abilities to reason about causes. It adds content and dimension to the trend of including embodied cognition in evolutionary studies and in the interpretation of the archaeological record. Our method could explain variation in technology sets between archaic and modern human groups.